Constructive games increase children's creativity - Maharani, Laila; Nopriansyah, Untung; Rahmawati, Widia; Harjani, Haryanti Jaya; Nufus, Ajijah Sadiah (Universitas Islam Negeri Raden Intan Lampung, 2022)
Creativity has a negative impact if children's basic abilities are not developed early. Children's activities that still tend to be monotonous cause children to get bored easily. This study aimed to determine the level of creativity in early childhood through constructive games at Mutiara Hati Kindergarten, Bandar Lampung. The activities can positively influence children's creativity, so the happier children are in play, the better their creativity will be. This research is a case study research involving three teachers and 15 students. The data were collected through observation, interviews, and document analysis to be analyzed qualitatively using data reduction, display, and concluding. The results showed that children's creativity could be increased through constructive games where they can imagine carrying out these activities so that their creativity develops according to their age. Furthermore, constructive games give children the freedom to explore their potential. Children's creativity is marked by increasing their understanding of the process of constructive play by playing with blocks and plasticine.